Eriodictiol protege camundongos submetidos à isquemia cerebral focal permanente, do dano neuronal, déficit de memória e resposta inflamatória - Ferreira, Emerson de Oliveira (2015)
Stroke is defined as a clinical neurological deficit that may last or exceed the first twenty - four hours of the event. The World Health Organization (WHO) reveals that between 2000 and 2011, the Stroke was pres ented as the second leading cause of death worldwide. According to the Ministry of Health, stroke is the leading cause of death in Brazil. It is caused by decreased blood perfusion depleted of oxygen and glucose to the brain, causing ATP reduction levels a nd predisposing to events such as glutamatergic excitotoxicity, exacerbated influx of Ca ++ , oxidative stress, inflammation and apoptosis, resulting in neuronal death. The eriodictyol (3 ', 4', 5,7 - tetrahydroxyflavanone) is a flavonoid found in the Chinese herb ( Dracocephalum rupestre ) having anti - inflammatory, antioxidant and anti - apoptotic effects previously reported. The objective of this study was to analyze the effects of eriodictyol on neuronal damage, memory deficits and inflammatory - response of mice subjected to focal cerebral ischemia by permanent meddle cerebral artery occlusion (pMCAO). The animals were treated orally with eriodictyol (1, 2 and 4 mg / kg) or vehicle (5% Tween 80 in saline 0,9%) 30 minutes before, 2 hours after the pMCAO and daily f or 4 days. The promoted pMCAOischemic brain damage in animals, this being confirmed by means of detection of a significant increase in the percentage of infarcted areas, the observed sensorimotor deficits and loss of neuronal viability. The eriodictyol red uced the area of cerebral infarction in doses of 1, 2 and 4 mg / kg and prevented the animal - ischemic neurological deficits 24h post - pMCAO. Also, prevented these animals of loss neuronal viability at dose of 4 mg/kg 96h after pMCAO. The animals submitted t o pMCAO showed a significant reduction in the number of rearings (open field test) and working (Y - maze) and aversive memory (passive avoidance test) deficits 72 and 96h after pMCAO. Treatment with eriodictyol the doses of 2 and 4 mg / kg normalized rearing s number at the doses of 1, 2 and 4 mg/kg prevented the working memory deficits, and a dose of 4 mg/kg prevented the memory aversive deficits. The pMCAO induced increase in MPO activity in the temporal cortex, induced TNF - α , iNOS and GFAP immunoreactivity in the temporal cortex and striatum in - ischemic animals. The eriodictyol at a dose of 4 mg/kg prevented the increase in MPO activity and increased of TNF - α , iNOS and GFAP immunoreactivity. The results of this study show that eriodictyol has neuroprotective activity in animals subjected to pMCAO and that this action is related at least in part to its antiinflammatory property.